State-of-the-Art Research on “Lymphomas: Role of Molecular Imaging for Staging, Prognostic Evaluation, and Treatment Response” - Kostakoglu, Lale; Cheson, Bruce D. (Frontiers in Oncology, 2013)
Lymphomas are heterogeneous but potentially curable group of neoplasms. Treatment of lymphomas has rapidly evolved overtime with significant improvement in the cure rate and reductions in treatment-related toxicities. Despite excellent results, treatment programs are continued to be developed to achieve better curative and safety profiles. In these patients individualized therapy schemes can be devised based on a well-defined risk categorization. The therapy efficacy can be increased early during therapy in non-responding patients with escalated therapy protocols or with the addition of radiation therapy, particularly, in advanced-stage or unfavorable risk patients. The increasing availability of positron emission tomography using 18F-fluorodeoxyglucose, particularly fused with computed tomography (FDG-PET/CT) has lead to the integration of this modality into the routine staging and restaging for lymphoma with convincing evidence that it is a more accurate imaging modality compared with conventional imaging techniques. FDG-PET/CT is also is a promising surrogate for tumor chemosensitivity early during therapy. This review will summarize published data on the utility of FDG-PET/CT imaging in the staging, restaging, and predicting therapy response in patients with lymphoma.